The effect of line balancing on the efficiency and effectiveness of shoe production at PT Wangta Agung - Hartono Subagio (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Business competition is increasing, companies must reorganize their business strategies and tactics every day in the era of globalization. The purpose of this study was to determine the effect of Line Balencing on the efficiency and effectiveness of shoe production at PT Wangta Agung. The research method used is descriptive research. Descriptive research is a type of research conducted with the main purpose of providing an objective description or description of the situation. The results of the research on the actual shoe production workstation configuration consisted of 15 work stations with a cycle time of 16 seconds. Analysis of sewing activity work time takes about 23.75 minutes for one additional operator to assist the two main operators in meeting the set targets. The increased capacity of the shoe-making production workstation consists of 7 stations that have a balance of 16 seconds of delay time with production efficiency with a yield of 87.5%.